Removable prostheses improve OHRQL and satisfaction of elderly people with rheumatoid arthritis - Bruna Fernandes Moreira Alfenas; Kelly Machado de Andrade; Talita Malini Carletti; Renata Cunha Matheus Rodrigues Garcia (Universidade Estadual de Campinas, 2020)
Rheumatoid arthritis (RA) is an autoimmune disease that affects joint tissues and causes severe physical and functional impairments on quality of life due to muscular and articular pain. The involvement of temporomandibular joint in RA interferes with mouth opening and masticatory process. However, no studies addressed the impact of RA on oral health-related quality of life (OHRQoL) and satisfaction with prostheses use in elderly people. Aim: This study assessed the impact of oral rehabilitation with conventional dentures on the OHRQoL and prostheses satisfaction in elderly patients with RA, associated or not with temporomandibular disorder (TMD). Methods: Forty-five elderly were enrolled and divided into three groups: (1) RA and TMD (n=15, experimental), (2) RA without TMD (n=15, experimental), and (3) without RA and without TMD (n=15, control). The OHRQoL and the prostheses satisfaction were evaluated before and after new oral rehabilitation with partial and/or complete dentures. The OHRQoL and prosthesis satisfaction were assessed and verified through OHIP-14 questionnaire and visual analogue scale, respectively. Results: TMD group exhibited the worst mean values (P<0.05) for all OHIP-14 domains before insertion of new dentures. Group 2 showed worst means (P<0.05) compared to controls for functional limitation and physical pain domains of the OHIP-14, but not in the general score. Patients showed better outcomes of satisfaction with prostheses use only after the new rehabilitation. Conclusion: The use of new and well-fitted dentures improves all domains of OHRQoL in patients with RA and TMD and all groups were satisfied with prostheses use after the new rehabilitation with conventional dentures.